The Three-Dimensional Ultrastructure of the Human Alveolar Epithelium Revealed by Focused Ion Beam Electron Microscopy - Jan Philipp Schneider (International Journal of Molecular Sciences, 2020)
Thin type 1 alveolar epithelial (AE1) and surfactant producing type 2 alveolar epithelial (AE2) cells line the alveoli in the lung and are essential for normal lung function. Function is intimately interrelated to structure, so that detailed knowledge of the epithelial ultrastructure can significantly enhance our understanding of its function. The basolateral surface of the cells or the epithelial contact sites are of special interest, because they play an important role in intercellular communication or stabilizing the epithelium. The latter is in particular important for the lung with its variable volume. The aim of the present study was to investigate the three-dimensional (3D) ultrastructure of the human alveolar epithelium focusing on contact sites and the basolateral cell membrane of AE2 cells using focused ion beam electron microscopy and subsequent 3D reconstructions. The study provides detailed surface reconstructions of two AE1 cell domains and two AE2 cells, showing AE1/AE1, AE1/AE2 and AE2/AE2 contact sites, basolateral microvilli pits at AE2 cells and small AE1 processes beneath AE2 cells. Furthermore, we show reconstructions of a surfactant secretion pore, enlargements of the apical AE1 cell surface and long folds bordering grooves on the basal AE1 cell surface. The functional implications of our findings are discussed. These findings may lay the structural basis for further molecular investigations.